(untitled) (Research, Society and Development, 2022)
Over the last decades, the discussion about actions and factors that favor a more effective communication of elderly individuals with hearing loss has become the goal of many professionals. Objective: Analyze the vision of elderly people with hearing loss, users and non-users of hearing aids, about factors that influence their social participation. Method: The participants of this research were recruited in a speech therapy clinic-school accredited to SUS, located in the southern region of Brazil, and were divided into 2 groups: Group 1 n=51 - elderly with hearing loss hearing aids users, and group 2 n=31 - elderly with hearing loss non-users of individual sound amplification devices (HA). The following instruments were applied:1) questionnaire to delineate the sociodemographic characteristics of the two populations, 2) international instrument (LIFE H 3.1) and 3) questionnaire (HHIEs). Results: Some factors that interfere with the social participation of elderly people of both groups, precarious housing, low retirement, few financial resources that hinder access to health. In the application of the HHIEs, no significant differences were found between the groups; however, in the LIFE-H 3.1, significant differences in the intersection with hearing loss in Group 01 for the area of Communication, and in Group 02 for the areas of Physical Conditioning and Education (p=0.36). Conclusion: The lack of resources can lead the elderly with hearing loss to a life without leisure and healthy interactions. HA proved to be an important device for the elderly with hearing loss to improve their social relations and interactions with others.